The effect of game-based education on adherence to treatment and anxiety level in type 2 diabetics started on insulin therapy - Esin Erdem; Gönül Düzgün (PLoS ONE, 2026)
Background Insulin initiation in type 2 diabetes mellitus (T2DM) is often hindered by anxiety and poor treatment compliance. Although game-based learning may enhance patient engagement, evidence regarding its effectiveness in adult populations remains limited. Objective To evaluate the effect of a game-based education program on treatment compliance (primary outcome) and anxiety levels (secondary outcome) in adults with T2DM receiving insulin therapy. Methods This randomized controlled study included 72 adults with T2DM who were assigned to either a game-based education group (n = 36) or a standard lecture-based education group (n = 36). Treatment compliance was assessed using the Patient Compliance Scale for T2DM Treatment (primary outcome), and anxiety was measured using the Beck Anxiety Inventory (secondary outcome). Between-group differences were analyzed using baseline-adjusted ANCOVA, controlling for baseline scores, age, duration of diabetes, and employment status. Exploratory correlation analyses examined the association between anxiety and treatment compliance. Results Baseline demographic and clinical characteristics were comparable between the intervention and control groups (p > 0.05). Following the intervention, participants in the game-based education group demonstrated significantly higher treatment compliance compared with those in the control group. Baseline-adjusted ANCOVA revealed a significant between-group difference favoring the intervention group for total treatment compliance (F = 65.92, p < 0.001), indicating a substantial improvement associated with the intervention. Adjusted analyses also showed significantly lower post-intervention anxiety scores in the intervention group compared with the control group (F = 11.241, p < 0.001), with a large effect size (partial η² = 0.14). Improvements were observed across most treatment compliance sub-dimensions, with the exception of lifestyle change, which did not reach statistical significance. Exploratory correlation analyses further indicated that the negative association between anxiety and treatment compliance weakened following the intervention only in the game-based education group, whereas this relationship remained significant in the control group. Conclusion Game-based education is more effective than standard lecture-based education in enhancing treatment compliance and reducing anxiety among individuals initiating insulin therapy. Additionally, the intervention may attenuate the adverse impact of anxiety on adherence-related behaviors. Trial registration ClinicalTrials.gov NCT07195188